2021
DOI: 10.24191/myse.v8i1.12662
|View full text |Cite
|
Sign up to set email alerts
|

Architectural Characteristics of Malay Traditional Houses Through Decorative Elements: A Comparison Between Perak Limas' House (Plh) and Johor Limas' House (Jlh)

Abstract: Malay Traditional houses were classified based on roof design, spatial organization, construction method, geographical setting and decorative elements particularly at every state in Malaysia. This article analyzes decorative elements on the traditional Malay houses in two states; Perak Limas' House (PLH) in Perak and Johor Limas' House (JLH) in Johor. The research aim is to establish the architectural characteristics of both PLH and JLH. This can be achieved by identifying the existence of decorative elements … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The main characteristics of vernacular style include the flexibility of space layout and construction materials as well as elevated floors. Lim (1987) and Rashid et al, (2021) added on the construction of vernacular buildings that incorporate occupants' culture and reflect a good understanding of nature and the environment. Moreover, Roche (2001) suggested that…”
Section: Introductionmentioning
confidence: 99%
“…The main characteristics of vernacular style include the flexibility of space layout and construction materials as well as elevated floors. Lim (1987) and Rashid et al, (2021) added on the construction of vernacular buildings that incorporate occupants' culture and reflect a good understanding of nature and the environment. Moreover, Roche (2001) suggested that…”
Section: Introductionmentioning
confidence: 99%
“…Limas house has grown even more expansive and spread outside South Sumatra, such as to Jambi, Lampung, Bengkulu, and Bangka Belitung areas [4]. Even so, the name of the limas house in Sumatra must be distinguished from the limas house in Malaysia [5], which is a traditional house of Negeri Perak [6] because it has a different architecture and philosophy. Currently, the existence of limas houses on the coast of the Musi River in Palembang has become an identity that characterizes the uniqueness of this city [3].…”
Section: Introductionmentioning
confidence: 99%